Tumoral Calcinosis in Distal Femur: First Documented Case in a Tertiary Medical Center in Philippines - Shah, Manish Bikram; June, Malana; Marco-Paolo, Lasam (Annapurna Journal of Health Sciences, 2023)
Tumoral calcinosis is a rare clinical and histopathologic syndrome characterized by calcium phosphate deposition in peri-articular soft tissue regions, most commonly in the large joints of the hips, shoulders, and elbows. We present the case of a 49-year old female with 8 months history of gradual increasing, painless swelling along her left distal thigh. Plain radiography demonstrated a dense lobulated cluster of calcific nodules within soft tissues consistent with a diagnosis of tumoral calcinosis, as confirmed by histopathological examination. Using this case as illustration, the first case of such nature in our institution, we reviewed pertinent literature related to the management of tumoral calcinosis. Although the pathogenesis in tumoral calcinosis is controversial, the ideal management is surgical excision with complete removal of abnormal tissue to prevent recurrence and to focus on the reduction of serum phosphate levels.